Discovery of Pneumonia Sufferers in Toddlers in Aceh Province - Ummu Nurainun; Rismah Aulia; Sasmita Megasari; Sri Savira; Sri Hayu Rahmatia (Journal of Epidemiology and Health Science, 2025)
Background: Pneumonia is an acute respiratory infection that attacks lung tissue, especially the alveoli. This disease can be caused by various microorganisms, such as bacteria, viruses, and fungi. Among vulnerable age groups, toddlers are one of the groups most at risk for serious complications from pneumonia. Therefore, efforts to control pneumonia in toddlers are a top priority in public health programs. Objective: This study aims to distribute the Discovery of Pneumonia Patients in Toddlers in Aceh province in 2022 Methods: This study used a quantitative descriptive method with secondary data analysis obtained from the Aceh Provincial Health Profile document. The data analyzed included Pneumonia Patients in Toddlers in Aceh province in 2022. Results: Based on data from the Aceh Provincial Health Office in 2022, the coverage of pneumonia cases in toddlers shows variations between districts/cities. Some areas show fairly high coverage, while others are still low. This indicates that there are differences in the implementation of early detection programs and reporting of pneumonia cases in toddlers at the local level. In general, although there has been an increase compared to the previous year, the coverage of case discovery has still not reached the national target in most regions. Conclusion: The coverage of the discovery of pneumonia cases in toddlers in Aceh Province in 2022 shows that control efforts have begun to run, but they are not evenly distributed throughout the region. Capacity building for health workers, public education, and stricter monitoring is needed to improve early detection and case reporting. Appropriate and rapid intervention is crucial in reducing the number of illnesses and deaths due to pneumonia in children under five.